Wide range analysis of ozone gas concentration in ultraviolet region - Yaacob, Maslina (2016)
The purpose of this research is to investigate the development of optical gas sensor employing absorption spectroscopy technique for ozone concentration measurement. Additionally, wide range analysis has been conducted to improve range of ozone concentration measurement using ultraviolet light absorption. Simulation of ozone absorption cross section in ultraviolet region was conducted via Spectralcalc.com® simulator. Simulation result for ozone absorption cross section was then verified by comparison with result from previous studies, showing small percentage of difference less than 3.05 %. In addition, the simulator was also used to investigate the effect of pressure and temperature on ozone absorption cross section. Simulation result showed ozone absorption cross section to exhibit negligible effect of pressure and temperature from 0.1 atm until 2.0 atm and from 293 K until 305 K, respectively. Next, path length of gas cell that suits with detection range of ozone monitor was determined through Spectralcalc.com® simulator. Finally, transmissive type gas cell is fabricated at optimum length of 10 cm. Based on the experiment results wide range analysis was conducted at 10 cm gas cell by consideration of less relative error of concentration. It was observed that wavelengths at 232 nm, 233 nm, 234 nm, 235 nm, 236 nm, 284 nm, 285 nm, 286 nm and 287 nm exhibit capability to measure ozone concentration using ultraviolet light absorption at high concentration value with wide range of concentration measurement from 619 ppm until 932 ppm. Of this, 285 nm was chosen due to its high resolution value at 17 ppm. The sensor exhibits fast response time and recovery time, both at 20 s. Peak of ozone absorption cross sections were observed in both experiment and simulation, located at 260.45 nm and 255.44 nm, respectively. Meanwhile, the values of peak of ozone absorption cross section were observed in experiment and simulation at 164.37 × 10-23 m2 molecule-1 and 114.86 × 10-23 m2 molecule-1, respectively. Significantly, this research has successfully demonstrated possibility of conducting wide-range analysis employing consideration of less relative error concentration. Particularly, vast improvement range of ozone concentration measurement has been achieved by wavelength selection which is far from the peak of ozone absorption cross section.